The Impact of Entrepreneurial Climate on the Entrepreneurial Intention of Physical Education Students: The Mediating Role of Creative Thinking - Mohamad Hasan Peymanfar; Najaf Aghaei; Zahra Zarei Mahmudabadi; Brett Anderson (Sports Business Journal)
Purpose: This study aims to examine the effect of the entrepreneurial climate on the entrepreneurial intentions of students enrolled in physical education colleges in Yazd Province, Iran, with creative thinking as a mediating variable.Methodology: This study employed path analysis and correlational methods. The statistical population comprised 314 male and female students from Yazd Province, Iran, and physical education schools. Based on Morgan’s table, a sample of 172 students was selected, and their completed questionnaires were included in the analysis. Data were collected using three instruments: Kang et al.’s (2019) Entrepreneurial Climate Questionnaire, Liñán et al.’s (2011) Entrepreneurial Intention Questionnaire, and Moghimian and Amini’s (2009) Creative Thinking Questionnaire. Statistical analyses were conducted using SPSS version 26 and Smart PLS version 3, with the significance level set at α = .05.Findings: The findings of this study indicate that creative thinking serves as a mediating variable in the relationship between entrepreneurial climate and entrepreneurial intention among students attending physical education colleges in Yazd, with a path coefficient of 2.907. The entrepreneurial climate demonstrated a significant direct effect on students’ entrepreneurial intention at the α = .05 level, accounting for 16.7% of the variance. Creative thinking also significantly impacted entrepreneurial intention (α = .05), contributing 12.0% to the explained variance. Additionally, the entrepreneurial climate significantly and directly influenced students’ creative thinking at the α = .05 level, with an effect size of 10.7%.Originality: This study explores whether individuals operating within an entrepreneurial environment can develop creative capacities and choose to pursue entrepreneurship. Specifically, it examines the relationship between the entrepreneurial climate, innovative thinking, and entrepreneurial intention.